THE EFFECT OF HANGMAN GAME TOWARDS STUDENTS’ VOCABULARY MASTERY AT THE SEVENTH GRADE STUDENTS OF MTS HIFZIL QUR’AN MEDAN IN THE ACADEMIC YEAR OF 2020/2021 - PUTRI RAMADHANI RAMADHANI (Faculty of Tarbiyah nad Teacher Training, 2022)
Vocabulary is one of the most basic elements of language learning that students have to master. Therefore, students are hoped to be able to understand the meaning of the words correctly. But in fact, the researcher found that students’ ability in vocabulary was still low. Using the appropriate technique will help students acquire more vocabulary. Hangman game is considered to be one of the most effective techniques to improve students’ vocabulary mastery. The formulations of this research problem as follows: 1) How are the students’ vocabulary mastery before being taught using Hangman game? 2) How are the students’ vocabulary mastery after being taught using Hangman game? 3) Is there any significant difference in students’ vocabulary mastery between students who are taught by using Hangman games and those who are taught by using the conventional technique? The method used in this study is quantitative method with quasi experimental research design. The researcher chose VII-2 as the experimental class and VII-3 as the control class. The findings of this research show that teaching vocabulary using Hangman games technique was effective. It can be seen by the t- value (3,649) is higher than t-table (2,024) with 5% (0.05) significance level and the Sign. (2 tailed) is 0.001 with alpha (α) was 0.05 (0.000 < 0.05). Hence, Ho (Null Hypothesis) was rejected and Ha (Alternative Hypothesis) was accepted. It showed that there was a significant difference using the Hangman games technique on student vocabulary mastery.